Indonesian Teachers’ Professional Development Practices and Needs in Post Pandemic Education - Sary Silvhiany (Universitas Hamzanwadi, 2022)
COVID19 pandemic has affected education sector in multiple ways, particularly in how teachers and students interact in the formal schooling. While virtual teaching has been widely expected as the new normal in this unprecedented time, little is known about how teachers grapple with the realities of this new mode of teaching learning and what their professional development needs are in this context. This article explores teachers’ perspectives on their professional development needs in the post pandemic era through the qualitative survey conducted with 265 Indonesian teachers who taught English in the elementary school, middle school, high school, and college level. Findings of this study showed that teachers used various online platforms to facilitate the online learning. However, less than half of the teachers in this study considered their teaching online effective. The teachers’ main concerns regarding the online learning include their students’ inability to fully participate in online learning and that their online learning was not as effective as their face to face learning. The teachers relied on attending webinars as one of the ways to do professional development. They also joined teachers’ learning communities to discuss new innovation in English language teaching, to get teaching materials they needed, to collaborate with other English teachers, and to share ideas about teaching English. Implication of the study includes the need for creating a virtual space for teachers to learn and exchange ideas with other teachers as a form of continuing professional development.